2005
DOI: 10.1111/j.1525-139x.2005.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis RoundsA Dialysis Case Presentation and DiscussionEdited by Roger A. Rodby : Long‐Term Intravenous Sodium Thiosulfate in the Treatment of a Patient with Calciphylaxis

Abstract: Calciphylaxis is a disabling and life-threatening complication that primarily affects patients who are dialysis dependent. This disease entity is characterized by calcification, intimal hypertrophy, and thrombosis of small vessels, which results in necrotizing, nonhealing ulcers. The development of these lesions portends a grim prognosis, as they are often accompanied by severe and sometimes fatal infectious complications. Although several strategies aimed at treating and preventing this affliction have been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(22 citation statements)
references
References 16 publications
1
20
0
1
Order By: Relevance
“…area under the curve) until its removal by the subsequent dialysis session. Typically, 25 g is given intravenously over 1 h after each of the thrice weekly high-flux hemodialysis treatments [14,15,16]. We feel it is important that the dose be adjusted for dialysis clearance when utilizing more intense or frequent intermittent treatments or for continuous modalities [17] (table 2).…”
Section: Treatmentmentioning
confidence: 99%
“…area under the curve) until its removal by the subsequent dialysis session. Typically, 25 g is given intravenously over 1 h after each of the thrice weekly high-flux hemodialysis treatments [14,15,16]. We feel it is important that the dose be adjusted for dialysis clearance when utilizing more intense or frequent intermittent treatments or for continuous modalities [17] (table 2).…”
Section: Treatmentmentioning
confidence: 99%
“…In an anuric patient this way of elimination seems to be reversed and the serum half-life much increased, which might be an important precondition for the mechanism of chelating calcium from precipitated calcium salts in the vessels. Brucculeri et al [27] could convincingly show that in their anuric patient the serum half-life of STS was 478 min compared to 15 min in healthy controls. Concerning these results, they postulated that the primary way of elimination of STS is biliary secretion.…”
Section: Sts Used For the Treatment Of Calciphylaxismentioning
confidence: 99%
“…In all described cases up to now there has been no evidence of recurrence of disease or severe side effects of the treatment. The only adverse drug reactions were described by Brucculeri et al [27], reporting occasional mild nausea and sometimes a slight emesis. In addition, these authors reported that the intravenous application of STS had an impact on the patients’ acid-base status, developing anion gap metabolic acidosis, which could be compensated by using a high bicarbonate dialysate.…”
Section: Sts Used For the Treatment Of Calciphylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Two new principles of treatment have recently emerged: (i) control of hyperparathyroidism by treatment with calcium sensitizers (cinacalcet) [23,24] , and (ii) improving solubility of calcium and phosphate by sodium thiosulfate (STS) [25,26]. This drug, known as antidote in cyanide intoxication, was first used to prevent recurrence of calcium containing stones of the urinary tract [27], then in tumoral calcinosis [28] and, more recently, has been used in calciphylaxis [29,30].…”
Section: Introductionmentioning
confidence: 99%